2012
DOI: 10.2522/ptj.20100438
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Use of a Home-Based Exercise DVD in People With Huntington Disease: Participants' Perspectives

Abstract: The DVD was perceived to be suitable and supportive. The DVD could be appropriate for use in supporting people with HD to engage in exercise at home, either outside of therapy sessions or upon completion of a therapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 34 publications
2
42
0
1
Order By: Relevance
“…Judging by the magnitude of the improvement on the physical functioning subscale and the physical summary component of the Short Form 36 (i.e. the large effect sizes on these subscales) and the perceptions of the intervention reported by participants, 16 we suggest that lack of significance in the Short Form 36 may be related to either the small sample size or the duration of the exercise programme. The effect size of 0.8 that we calculated for the physical functioning subscale (see Table 2) suggests that we would have needed 42 participants in total to sufficiently power the study on this variable.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Judging by the magnitude of the improvement on the physical functioning subscale and the physical summary component of the Short Form 36 (i.e. the large effect sizes on these subscales) and the perceptions of the intervention reported by participants, 16 we suggest that lack of significance in the Short Form 36 may be related to either the small sample size or the duration of the exercise programme. The effect size of 0.8 that we calculated for the physical functioning subscale (see Table 2) suggests that we would have needed 42 participants in total to sufficiently power the study on this variable.…”
Section: Discussionmentioning
confidence: 89%
“…The latter is important, as reduced motivation is one of the core features of Huntington's disease. 27 Qualitative data from the intervention group, which is reported elsewhere, 16 revealed that commitment of the carer and supporting the relationship between the carer and the person with Huntington's disease were key elements to the success of the programme; the main reason for nonadherence in two participants was related to the commitment of the carer. This implies that finding strategies to maximize the successful engagement of the carers in supporting people with Huntington's disease in the home setting is required.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…13 Programs that are enjoyable, motivating, and home-based may overcome these barriers. 8 Research has shown that video game-based exercise increases practice volume, attention span and compliance compared with traditional exercise programs. 10,11 Video game play that included dynamic, coordinated exercise significantly improved balance, mobility, fall risk, and cognition in individuals with Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Additionally, a home-based strengthening exercise program was shown to improve gait and balance when supervised by a family member or caregiver. 8 However, apathy, depression, motor problems, and inadequate transportation present exercise barriers. 13 Programs that are enjoyable, motivating, and home-based may overcome these barriers.…”
Section: Introductionmentioning
confidence: 99%